EFEKTIVITAS DAN EFISIENSI MODAL KERJA DALAM MEMPENGARUHI PEROLEHAN RETURN ON ASSET PADA PERUSAHAAN SEMEN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Alhidayatullah Alhidayatullah (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2021)
This study aims to determine cash turnover, accounts receivable turnover, inventory turnover, working capital turnover in influencing return on assets (ROA) in cement companies listed on the Indonesia Stock Exchange for the period 2016 - 2019. This study uses an explanatory analysis method with a quantitative approach, namely a research method that intends to explain the position of the variable under study and the causal relationship between one variable and another through hypothesis testing and focuses on variable problems with concepts that have value and looking for relationships between these variables. Hypothesis test results show that cash turnover to ROA is tcount -1,204 <ttable 2,365 and sig t 0,268> 0,05, turnover of accounts receivable to ROA is calculated from tcount 0.078 <ttable 2.365, and sig t 0.940> 0.05, inventory turnover at ROA where the value of t count -1.099 <t table 2.365, and sig t 0.308> 0.05, and the turnover of working capital to ROA, the calculation is t count 0.628 <t table 2.365, and sig t 0.550> 0.05, which explains that all independent variables have no significant effect on ROA. While cash turnover, accounts receivable turnover, inventory turnover, and working capital turnover together (simultaneously) do not have a significant effect on return on assets, the calculation results show Fcount 0.672 <Ftable 4.120 and the significance is 0.632> 0.05. Based on the analysis of the coefficient of determination, the effect of cash turnover, accounts receivable turnover, inventory turnover, and working capital turnover on return on assets is 27.8%, the remaining 72.2% is influenced by other factors not examined.